(3TQM QSGdI aj GddZI GdYQHjIs - (3GdQhej, SQhQj CafOQj RGOg, eUdM GdOjf, eUWai Hf TYHGf, J (B969 (3g`s ((3HdGO bhfjI aj eOQSI NGfs)
(3ChdgG (B:s
(3dc GdMeO jG ef TQa fhY GdEfSGf hHYO aEf GdTjN aGVd deG Cda aj GdQSGFd GddZhjI ebOeI Cf CTQMgG TQMG HSe Gddg GdQMef GdQMje NHRGJc haj eN GdNHR eYQha hGdNHR HGdaJM GdeUOQs
(3BNQgG (B:s
(3bGd GdYHO GdPdjd jMji Hf fUhM Hf ESQGFjd eG hbY aj gPg GdQSGdI ef PcQ (B((3eN(B) (3aGdeQGO Hg eNJGQ GdUMGMheG hbY ef PcQ (B((3Lh(B) (3aGdeQGO Hg GdLhGeY heG hbY ef PcQ (B((3aG(B) (3aGdeQGO Hg aGFb GddZIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 234s
(3eYLe GdeDdajf(B: 3 / 866s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GddZIs